The Efficacy of Metal Artifact Reduction Mode in Cone-Beam Computed Tomography Images on Diagnostic Accuracy of Root Fractures in Teeth with Intracanal Posts - Dalili Kajan, Zahra; Taramsari, Mehran; Khosravi fard, Negar; Khaksari, Farnoush; Moghasem Hamidi, Forough (Iranian Endodontic Journal, 2019)
Introduction: The purpose of this study was to evaluate the efficacy of cone-beam computed tomography CBCT in the diagnosis of RF in the presence of an intracanal posts with and without applying “metal artifact reduction” (MAR) mode. Methods and Materials: This in vitro study included 60 single-canal endodontically treated premolars. Post spaces were created in all roots. RFs were simulated in 30 of the 60 teeth. Dentatus posts were cemented in 15 of 30 roots with and without RFs. Teeth were arranged randomly in 6 artificial dental arches. Images were taken using a Vatech CBCT machine with and without MAR (MAR and WMAR, respectively). A radiologist and an endodontist evaluated the CBCT images for the presence of RFs. Sensitivity, Specificity, positive and negative predictive values were determined for each mode. MC Nemar’s and Kappa tests were used for data analysis. Results: The percentage of correct diagnosis using the WMAR mode in both the post space and pin groups in the presence of root fracture was 46.6%; with MAR, it increased to 86.6% and 66.6%, respectively. There was no significant difference between two modes in post space (P=0.503) and metal pin groups (0.549). The overall sensitivity of VRF diagnosis in WMAR mode was 46.67%; in MAR mode, sensitivity was 76.67%. The specificity of WMAR and MAR modes were 60% and 53.33%. The levels of agreement between two modes and real findings were less than 0.45. Conclusions: There were no significant differences between the efficacies of imaging modes. The sensitivity of the MAR mode for diagnosis of VRF in both the pin and post space groups was higher than the WMAR mode. The specificity of MAR in comparison with WMAR was less or equal in dental groups. The agreement between CBCT and real findings was poor. Keywords: Artifact; Cone-Beam Computed Tomography; Diagnosis; Tooth Fracture; Vertical Root Fracture